Morphotectonics of Shatt Al-Arab River Southern Iraq - Shakir Al-Kubaisi, Manal; A. Hussein , Meelad (Iraqi Journal of Science, 2023)
A morphotectonic analysis is conducted on Shatt Al-Arab drainage basin. This study aims to analysis of the river patterns of Shatt Al-Arab channel and their relationship with the development of subsurface geological structures and the neotectonic activity, as well as an attempt to determine the relative amount to this activity.Transverse river profile analysis is derived quantifiable and comparable parameters such as neotectonic index (Eh*Ln), Eh, Ch, and Bs. These parameters are useful to detect the morphotectonic indicators of Shatt Al-Arab basin. The analysis showed the role of the subsurface structures that affecting the river cross sections shape, through channel incision, as in (Dair and NuhrUmr) cross sections, while in the others the increasing in neotectonic index interpreted by the geomorphic features such as sudden changes or diversion in river course and river pattern changes.